Nepāḥdeyā Kanakacaityamahāvihārayā ashṭottarasata Lokeśvarayā paricaya - Bajrācārya, Amoghabajra (Lokeśvara Saṅgha, 1979)
Description of the paintings of one hundred aspects of Avalokiteśvara, Buddhist deity, preserved in the Kanakacaityamahāvihāra, Kathmandu, Nepal; includes legends associated with the deity.